New species of cynipid inquiline, Saphonecrus kuriphilusi (Hymenoptera: Cynipidae: Synergini), from Dryocosmus kuriphilus galls in Greece - Melika, George; Memtsas, George I.; Nicholls, James A.; Avtzis, Dimitrios N. (Zootaxa, 2018)
Since Dryocosmus kuriphilus (Hymenoptera: Cynipidae) emerged worldwide as a dangerous pest of chestnuts, there is only one dubious record from Japan of a cynipid inquiline reared from its galls. This is the first comprehensively documented record of a cynipid inquiline, Saphonecrus kuriphilusi, new species reared from galls of D. kuriphilus in Greece. Morphological description, morphological and molecular diagnostic characters for the new species are given.